Challenges in Developing Evidence-Based Recommendations Using the GRADE Approach: The Case of Mental, Neurological, and Substance Use Disorders - Barbui, Corrado (Public Library of Science, 2010)
Corrado Barbui and colleagues describe their use and adaptation of the GRADE approach in developing the guidelines for the WHO mental health Gap Action Programme (mhGAP).